Educational Policy in the Post-racial Era: Federal Influence on Local Educational Policy in Hawaii - Tanabe, Clifton S. (Paideusis, 2010)
On March 27, 2008, Newsweek ran an article titled, “Obama’s Postracial Test: How will the Democratic Candidate Deal with Potentially Divisive Ballot Initiatives Calling for an End to Affirmative Action?” And, the August 6, 2008 issue of the New York Times Magazine featured an article titled, “Is Obama the End of Black Politics?” Since then, writers from the right and left have raised and challenged the idea that the election of Barack Obama somehow signals a new, post-racial era and presidency. But what does this mean for Hawaii? With its unique racial diversity and its connection to Obama, might Hawaii somehow represent the first post-racial state? And, does this mean anything for the way education is run in that state? In addressing these questions, this paper looks carefully at the Obama Administration’s recent education initiative called the Race to the Top Fund and examines its implications for education in Hawaii.